The use of estimates of heritability and genetic variances in selection for chip colour between potato populations - Domański , Leszek; Zimnoch-Guzowska, Ewa; Domańska, Maria (Plant Breeding and Seed Science, 2006)
The objective of this research was to examine the expected responses to selection for colour of chips (= crisps) produced directly from tubers stored at 4-6°C for three months in three potato populations. Population 1 was obtained from crossing cv. Lady Claire with parental line M-62774, Population 2 was derived from crossing cv. Snowden with parental line M-62724. Both populations originated from crosses between cold chipping parents. Population 3 was produced by intermating cold chipping parent (cv. Snowden) with good chipping parent (M-62805) that requires the reconditioning treatment. Fifty-eight to sixty random clones for each population plus four parents and four control cultivars were planted in 2003 and 2004 at M³ochów Research Center of Plant Breeding and Acclimatization Institute. A considerable genotypic variation in chip colour after cold storage has been found within three hybrid populations. Heritability estimates were moderate, ranging from 0.42 to 0.53, and each of these populations exhibited good potential advance by selection for chip colour after cold storage.